Remaining coverage in associative desorption process - Furlong, Octavio Javier (2004)
In this paper the kinetic of dissociative adsorption of dimers followed by associative desorption is analyzed. The coupled differential equations which describe the kinetics of the process were obtained by applying the so-called local evolution rules. Particular interest presents the irreversible desorption process. In fact, given that desorption proceeds from the reacting nearest-neighbor monomers, a remaining coverage results from those isolated particles when the mobility is neglected, therefore, the resulting configuration can be considered as a jamming state of the system. The exact solution for the remaining coverage is obtained in one-dimensional chain, where the effect of the lateral interactions are also included. The two-dimensional case is analyzed by using Monte Carlo simulation. The equilibrium solutions and the thermal desorption spectra are also studied.